GHFHC: Generalized Hesitant Fuzzy Hierarchical Clustering Algorithm - Aliahmadipour, Laya; Eslami, Esfandiar (International journal of intelligent systems, 2016)
Dealing with uncertainty is an undeniable challenge in the real‐world problems. In this paper, we focus on hesitant environment such as generalized hesitant fuzzy sets introduced by Qian et al. So we propose a new generalized hesitant fuzzy hierarchical clustering (GHFHC) algorithm based on Atanassov's intuitionistic fuzzy set theory. We extend conventional hierarchical clustering, which just works on the crisp data, and introduce a clustering algorithm, which can be applied on large data set with generalized hesitant fuzzy data. The run time of the GHFHC algorithm shows that its computational complexity will be low. Also, the GHFHC algorithm produces the clusters with arbitrary shapes by using the various distance measures. Finally, an example is provided to illustrate the practicality of the proposed algorithm.